Organic Fertilization Leads to N Limitation Rather than P Limitation in Both Vegetable Soils - Qingshan Li; Mengqian Xu; Lingying Xu; Xingwang Wu; Yuqin Zhang; Jia Xin; Yazhen Shen; Jichao Gao (Agronomy)
Organic amendments are widely used to enhance soil fertility and nutrient cycling in greenhouse cultivation, but their effectiveness can vary depending on their origin and composition. This study investigated the impact of four organic materials (rice husk, coconut coir, biochar, and sheep manure) on nutrient cycling and enzyme activities in two of greenhouse tomato soils. The distribution of soil nutrients and enzyme activities was analyzed under controlled conditions during a pot experiment. The addition of organic amendments, regardless of their source, significantly altered the microbial resource allocation, reducing the carbon limitation while increasing the nitrogen demand. The effect on soil nutrient pools was largely determined by the chemical composition of the amendments. In clayey soils, biochar and rice husk additions most effectively promoted enzyme activities related to carbon, nitrogen, and phosphorus acquisition. Under sandy soil conditions, sheep manure increased carbon and phosphorus acquisition enzymes, while biochar most effectively enhanced nitrogen acquisition enzymes. Biochar emerged as a particularly effective amendment, enhancing organic carbon sequestration across different soil types. The chemical composition of the amendments, specifically, the content of carboxyl C, aromatic C, and O-alkyl C, played a crucial role in influencing soil nutrient limitations. In clayey soils, the mean C:N:P ratios for CK, T1, T2, T3, and T4 treatments were 1:1.375:0.625, 1:1.244:0.662, 1:0.839:0.610, 1:1.161:0.689, and 1:1.038:0.549, respectively. In sandy soils, the ratios were 1:1.117:0.698, 1:1.18:0.75, 1:1.096:0.731, 1:1.217:0.689, and 1:1.06:0.669, respectively. These findings suggest that the addition of organic amendments can improve nutrient retention and enzyme activities, but their effects on soil nutrient pools are influenced by both the composition of the amendments and the soil texture. This research enhances our understanding of organic amendments and soil nutrient transformations, and aids in optimizing the application of organic materials for improved soil management in greenhouse cultivation.